The Account of Crimea and the Crimean Khanate Produced by William Tooke in 1785 - N.I. Khrapunov (Золотоордынское обозрение)
Research objective: This paper analyses a little-known source, the account of British traveller William Tooke, describing his journey though Russia in 1785, which supplies information on the Crimea and the Crimean Khanate. Research materials: This paper addresses Tooke’s letters to the editor of the London-based Gentleman’s Magazine – a source previously not used by Russian scholarship. This was the first publication which informed a British audience about the Crimea after its first joining to Russia. Research novelty and results: This paper reveals that Tooke received his information on the Crimea primarily from the account of the employee of the Russian Academy of Sciences, Vasilii Zuev, who visited it in 1782. The British author then added to it the data excerpted from the work by Swedish Johann Thunmann, and also his own information gathered from Russian sources. Tooke’s letters allow one to understand the beginnings of the research investigation of the Crimea, the European intellectuals’ ways of understanding the region’s economic potential and approaches to its development, their approaches to sources, the stereotypes burdening their understanding of the area and its culture, and the information on the distant northern Black Sea area obtained by European society in the period in question. Tooke’s work is a good example of the transfer of ideas between Russia and Western Europe, when the Crimea was not only the subject of learning but also a kind of “mirror” which allowed those who researched it to understand their own culture in a deeper way.